Implementasi Program PKK Bidang Pemberdayaan Pendidikan Dalam Meningkatkan Kesejahteraan Masyarakat Di Desa Bandungsekaran Kecamatan Balongpanggang Kabupaten Gresik - Andriyani, Nuraini; Bayu Aulia Priyantomo; Mulus Sugiharto; Chintya Anggun Pratama; Shalasa Rafika Putri (Faculty of Social and Political Science, 2024)
The PKK Program for Educational Empowerment is a program that works to improve the welfare of society by improving the education of the youth generation in Bandungsekaran Village. In implementing this program, participation from the Bandungsekaran community is needed so that this program can be carried out well, while the people of Bandungsekaran Village themselves have very little literacy and even a low level of education because Bandungsekaran Village is one of the small villages in Balongpanggang District, Gresik Regency. The aim of this research is to analyze and understand the policies of the PKK program in the field of educational empowerment in Bandungsekaran Village, Balongpanggang District, Gresik Regency. The research method used is qualitative with a case study approach, data collection techniques using purposive sampling with six respondents and research stages through interviews, observation and documentation. The results of the research on the PKK program show that implementation has been achieved but has not been carried out optimally because socialization has not been carried out for the people of Bandungsekaran in the field of educational empowerment. People's knowledge and insight regarding education is still minimal, the people of Bandungsekaran prefer to work at a young age and do not want to study because according to them education does not guarantee people's lives while working as farmers and traders definitely guarantees life. So it can be concluded that this policy has not been implemented effectively and efficiently. The targeted output of this research is to create support and active community participation related to the PKK program in the education sector. Apart from that, this research is targeted to be able to create national seminar proceedings so that it will explore widely among the community about the Implementation of the PKK Program in the Field of Educational Empowerment in Improving Community Welfare in Bandungsekaran Village, Balongpanggang District, Gresik Regency.